Radial symmetry for a generalized nonlinear fractional p-Laplacian problem - Hou, Wenwen; Zhang, Lihong; Agarwal, Ravi P.; Wang, Guotao (Nonlinear Analysis: Modelling and Control, 2021)
This paper first introduces a generalized fractional p-Laplacian operator (–Δ)sF;p. By using the direct method of moving planes, with the help of two lemmas, namely decay at infinity and narrow region principle involving the generalized fractional p-Laplacian, we study the monotonicity and radial symmetry of positive solutions of a generalized fractional p-Laplacian equation with negative power. In addition, a similar conclusion is also given for a generalized Hénon-type nonlinear fractional p-Laplacian equation.